Characterisation and correlates of stunting among Malaysian children and adolescents aged 6–19 years. (4th March 2019) - Partap, Uttara; Young, Elizabeth H.; Allotey, Pascale; Sandhu, Manjinder S.; Reidpath, Daniel D.
Abstract: Background: Despite emerging evidence regarding the reversibility of stunting at older ages, most stunting research continues to focus on children below 5 years of age. We aimed to assess stunting prevalence and examine the sociodemographic distribution of stunting risk among older children and adolescents in a Malaysian population. Methods: We used cross-sectional data on 6759 children and adolescents aged 6–19 years living in Segamat, Malaysia. We compared prevalence estimates for stunting defined using the Centers for Disease Control and Prevention (CDC) and the World Health Organization (WHO) references, using Cohen's κ coefficient. Associations between sociodemographic indices and stunting risk were examined using mixed-effects Poisson regression with robust standard errors. Results: The classification of children and adolescents as stunted or normal height differed considerably between the two references (CDC v . WHO; κ for agreement: 0.73), but prevalence of stunting was high regardless of reference (crude prevalence: CDC 29.2%; WHO: 19.1%). Stunting risk was approximately 19% higher among underweight v . normal weight children and adolescents ( p = 0.030) and 21% lower among overweight children and adolescents ( p = 0.001), and decreased strongly with improved household drinking water sources [risk ratio (RR) for water piped into house: 0.35, 95% confidence interval (95% CI) 0.30–0.41, p < 0.001). Protective effects were also observed for improved sanitation facilities (RR for flush toilet: 0.41, 95% CI 0.19–0.88, p = 0.023). Associations were not materially affected in multiple sensitivity analyses. Conclusions: Our findings justify a framework for strategies addressing stunting across childhood, and highlight the need for consensus on a single definition of stunting in older children and adolescents to streamline monitoring efforts.